Non-welfarist optimal taxation and behavioral public economics - Ravi Kanbur; Jukka Pirttilae; Matti Tuomala (Center for Economic Studies and ifo Institute (CESifo), 2004)
Research in behavioral economics has uncovered the widespread phenomenon of people making decisions against their own good intentions. In these situations, the government might want to intervene, indeed individuals might want the government to intervene, to induce behavior that is closer to what individuals wish they were doing. The analysis of such corrective interventions, through taxes and subsidies, might be called ?behavioral public economics.? However, such analysis, where the government has an objective function that is different from that of individuals, is not new in public economics. In these cases the government is said to be ?non-welfarist? in its objectives, and there is a long tradition of nonwelfarist welfare economics, especially the analysis of optimal taxation and subsidy policy where the outcomes of individual behavior are evaluated using a preference function different from the one that generated the outcomes. The object of this paper is to first of all present a unified view of the non-welfarist optimal taxation literature and, secondly, to present behavioral public economics as a natural special case of this general framework.
Keywords: H23; H21; 330; non-welfarism; optimal taxation; behavioral economics; Optimale Besteuerung; Verhaltensökonomik; Finanzwissenschaft; Theorie